Light-curing of calcium hydroxide-based liners: pH analysis and calcium ion release - Paulo Fermino Costa Neto; Mariana Bena Gelio; Joissi Ferrari Zaniboni; Jardel Camilo do Carmo Monteiro; Adirson Jorge Júnior; Milton Carlos Kuga (Brazilian Dental Science)
Objective: Compare the pH values and calcium ion release of calcium hydroxide-based liner materials before and after light-curing. Material and Methods: The materials evaluated were: hydrox-cal white (HW), hydroxcal dentin (HD), Biocal (BC) and UltraBlend Plus (UB). 120 samples of the liner materials were inserted into a PVC tube (n=15). The samples from HW+A, HD+A, BC+A and UB+A were subjected to photoactivation. The other groups HW+N, HD+N, BC+N and UB+N were only inserted in a glass tube with deionized water. The pH was measured 24 hours and 14 days after the inclusion of the samples with the aid of a pH meter. The calcium release was analyzed with the aid of an atomic absorption spectophotometer at 24h and 14 days. The results were submitted to the Shapiro-Wilk test, followed by ANOVA and Tukey test (p=0.05). Results: In 24h, the groups that were not light cured showed the highest pH values (p<0.05). In 14 days, BC+N and BC+A demonstrated the lowest pH values. The groups that were not light cured also showed higher calcium release values in 24h and 14 days (p<0.05). Conclusion: Photoactivation of calcium hydroxide-based liner materials negatively interferes with calcium ion release, as well as with pH.